Spatial hazard models: limitations and applications - Brigitte Waldorf (European Regional Science Association (ERSA), 2002)
The paper develops an important spatial extension of longitudinal models. Longitudinal models capture variations in the timing of events. Recently, they have also been applied to variations in the spacing of events, using distance as a mathematical equivalent of time. Spatial relationships are, however, characterized by two-dimensionality, and distance alone is therefore insufficient for the assessment of their variations. The methodological extension defines spacing and spatial relationships via two dimensions and develops the associated mathematical and statistical apparatus using joint probability density functions of movement along both axes. The proposed extension will be applied to an empirical example, using data on spatio-temporal fertility patterns in Italy over the last three decades.
Keywords: 330